PASSIVE VOICE IN POLITICAL NEWSPAPER ARTICLES - Stojan, Nataša; Mijić, Sonja (PEOPLE: International Journal of Social Sciences, 2017)
The passive voice is a very challenging part of English grammar. The aim of this paper is to examine the function, frequency and structure of the passive voice in written language production. The study is carried out on a sample of twenty newspaper articles dealing with the US presidential campaign; ten articles are taken from the New York Times and ten articles from USA Today published in February and March 2016. The analysis of the articles from both newspapers includes the language of journalists and politicians. Furthermore, this paper provides a theoretical review of the passive voice according to traditional view of grammar, but it also outlines features of the passive voice within the framework of Cognitive Grammar. The findings have shown that the passive is commonly used in political newspaper articles and that it is not always possible to determine with certainty the function of the passive voice in short passive structures, be it that the agent is omitted because it is unknown, unimportant or obvious or whether the action is more important than the agent. Therefore, another aim of this paper is to investigate if some of the uncertainties regarding the functions of the passive voice can be tackled and explained better within the theoretical framework of Cognitive Grammar since it offers an interesting alternative to traditional grammatical analysis. In this way, the paper can contribute to the further study of this challenging linguistic field and provide incentive for similar studies comprising more examples from political or some other discourse.